IMPLEMENTASI PELAKSANAAN E-LEARNING DI ERA PANDEMIC COVID-19 (Studi Pada Prodi PG PAUD Universitas Bengkulu) - Rijki Agung Ramadhana (DIADIK, 2020)
This study aims to describe the implementation of  e-learning in the PG PAUD Study Program, Bengkulu University. The method used is descriptive qualitative. The informants in this study were 8 people involved in the implementation of e-learning. Techniques of collecting data by interview, observation, documentation. Based on the field findings, it can be results are: (1) The PG PAUD Study Program has prepared a policy  foundation  in  the  form  of  an  e-learning  implementation  mechanism,  with training. (2) Planning e-learning refers to what has been compiled from the syllabus. (3) The implementation of e-learning students can integrate learning with the implementation of e-learning. (4) Evaluation of e-learning is combined with academic information, evaluation, communication, discussion until the implementation runs well. (5) There are supporting factors such as: network, and inhibiting factors such as: signal, and internet pulse.